¿Es posible combinar lo tradicional con lo moderno? - Mansilla, Felipe (Revista de Filosofía, 2003)
Against fashionable postmodernist tendencies the author pleads for a combination of positive elements of premodern conceptions and reasonable modern features. He attempts to retrieve some factors of premodern societies and to blend them with the genuinely positive aspects of modernity. Among the former he points out religion as a source of sense and comfort. Similar syncretizing efforts in other fields constitute a fair portion of the history of mankind.